2013
DOI: 10.3852/13-101
|View full text |Cite
|
Sign up to set email alerts
|

Sexual reproduction in Aspergillus tubingensis from section Nigri

Abstract: A sclerotium-forming member of Aspergillus section Nigri was sampled from a population in a single field in North Carolina, USA, and identified as A. tubingensis based on genealogical concordance analysis. Aspergillus tubingensis was shown to be heterothallic, with individual strains containing either a MAT1-1 or MAT1-2 mating-type gene. Strains of opposite mating type were crossed on mixed cereal agar and incubated for 5-6 months. Stromata typically formed 1-2 indehiscent ascocarps containing asci and ascospo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
0
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 46 publications
4
30
0
1
Order By: Relevance
“…Evidence also suggests that sclerotia in Aspergillus might constitute 'sterile stromata' (Rudolph 1962). Nevertheless, recent studies have revealed that sclerotia of A. tubingensis in section Nigri Aspergillus niger and Aspergillus carbonarius in grape berries bore ascocarps containing ascospores very similar to the sexual stage in section Flavi as described for Aspergillus flavus (Horn et al 2013). However, since in this study, conidia were present internally, the morphogenesis of this structure approaches more that of a stroma rather than that of a sclerotium.…”
Section: Discussionmentioning
confidence: 77%
“…Evidence also suggests that sclerotia in Aspergillus might constitute 'sterile stromata' (Rudolph 1962). Nevertheless, recent studies have revealed that sclerotia of A. tubingensis in section Nigri Aspergillus niger and Aspergillus carbonarius in grape berries bore ascocarps containing ascospores very similar to the sexual stage in section Flavi as described for Aspergillus flavus (Horn et al 2013). However, since in this study, conidia were present internally, the morphogenesis of this structure approaches more that of a stroma rather than that of a sclerotium.…”
Section: Discussionmentioning
confidence: 77%
“…Beta tubulin ( BT2 ), calmodulin ( CF ), nuclear internal transcribed spacer region (ITS), DNA replication licensing protein ( Mcm7 ), RNA polymerase II ( RPB2 ) and ribosome biogenesis protein ( Tsr1 ) were amplified from 1∶10 diluted genomic DNA using previously described primers and conditions [21]. RNA polymerase II largest subunit ( RPB1 ) sequences were obtained for select isolates using published methods [4].…”
Section: Methodsmentioning
confidence: 99%
“…for distinct Aspergillus sections, as recommended by Pitt and Taylor (2014). If the latter solution to the nomenclatural problem in Aspergillus sensu Raper and Fennell (1965) was to be adopted, Aspergillus will have to be neo-typified, by for example A. niger (Pitt and Taylor 2014), because Aspergillus at Table 1 Sections of Aspergillus and their associated sexual states Subgenus/section Raper and Fennell (1965) group Earlier name given to the sexual state in the two-name system References on taxonomy, phylogeny and secondary metabolites Circumdati/Nigri Aspergillus niger group Saitoa, now informally saitoa-morph Parenicová et al 2001;Abarca et al 2004;Samson et al 2004;De Vries et al 2005;Serra et al 2006;Perrone et al 2007Perrone et al , 2008Samson et al 2007a, b;Varga et al 2007a;Noonim et al 2008;Nielsen et al 2009;Varga et al 2011a;Meijer et al 2011;Perrone et al 2011;Jurjevic et al 2012a, b;Hong et al 2013;Horn et al 2013 Circumdati/Flavi…”
Section: Taxonomy and Phylogeny Of Aspergillusmentioning
confidence: 97%